From disconnection to compassion: a phenomenological exploration of embodied empathy in a face-to-face interaction - Troncoso, Alejandro; Zepeda, Antonia; Soto, Vicente; Riquelme, Ellen; Fuentealba, Sissi; Andreu, Catherine; Cebolla, Ausiàs; Martínez-Pernía, David (Frontiers in Psychology, 2025)
BackgroundResearch has advanced in revealing psychological and brain mechanisms in empathy-compassion experience. However, much of this research has been constrained by using non-ecologically valid, non-interactive experimental paradigms, as well as a lack of in-depth investigation into participants’ subjective experiences.ObjectiveThis study aims to bridge these gaps by examining subjective experiences within an interactive setting.MethodsForty-two participants engaged in a 90-s, face-to-face interaction with an actor simulating a person with (Alzheimer’s) dementia. The actor’s performance in the interaction followed a validated emotion-inducing narrative about his fear of forgetting their family memories. Subsequently, micro-phenomenological interviews explored participants’ embodied experiences. Data underwent iterative inter-coder processing, and both qualitative and quantitative analyses were conducted. Qualitative analysis focused on temporal dynamics and multilayered dimensions (bodily, affective, attentional, motivational, and relational), while quantitative analysis assessed Bayes’s correlation between phenomenological dimensions and structures of experience, alongside exploratory correlations with empathy-compassion trait questionnaires.ResultsThe participants initially connect with the actor’s suffering in their own bodies, leading to an intensified sensation of anguish as the actor vividly describes the fear of forgetting his wife. After, four main experiential ways of navigating the anguish were identified: (1) Relational Disengagement, characterized by detachment from others’ suffering, reduced anguish intensity, and a cold interaffective space; (2) Persistent Angst, characterized by ongoing distress; (3) Anguish Anchoring, characterized by a reactive willingness to alleviate suffering, intense bodily sensations, fluctuating presence, and a less warm, more distant interaffective space; and (4) Compassionate Balanced Support, characterized by a felt presence within a warm interaffective space, motivating balanced support for others. These graded experiences were positively correlated with the ‘empathic concern’ trait assessed by the Interpersonal Reactivity Index scale.ConclusionThis study suggests a shift in empathy research by proposing moving from a traditional binary view (distress and compassion) to a nuanced framework identifying four distinct and holistic embodied experiences.